Can net photosynthesis and water relations provide a clue on the forest decline of Quercus suber in North Tunisia? - Lee, S. H.; Woo, S. Y.; Nasr, Z. (African Journal of f Biotechnology, 2011)
Net photosynthesis, sap flow density (SFD) and water use efficiency (WUE) were measured in a Quercus suber forest in north Tunisia in an attempt to explain the forest decline. In general, sap flow was positively related to light intensity and water loss, indicating that high light intensities can increase the SFD up to the saturation point in the cork oak. CO2 assimilation of cork oak in this region was light intensity-dependent. Cork oak showed a general increase in photosynthetic rates with increasing light intensity up to the light saturation point. Increased radiation probably increased the photosynthesis and growth above ground in this area, whereas the below-ground soil had insufficient moisture for uptake through the roots because the high light intensity and temperature induced high evapotranspiration.
Keywords: decline; evaportranspiration; light intensity; Quercus suber; sap flow density; water use efficiency

INFLUENCIA DEL CULTIVO DE LUPINUS LUTEUS L. EN LA DENSIDAD DE INÓCULO DE PHYTOPHTHORA CINNAMOMI EN SUELOS DE DEHESA - Serrano, M. S.; Sanchez, M. E.; De Vita, P.; CARBONERO, M. D.; Trapero, A.; FERNÁNDEZ-REBOLLO, P. (Actas de la XLVIII RC de la SEEP. Huesca La multifuncionalidad de los pastos: producción ganadera sostenible y gestión de los ecosistemas, 2009)
Phytophthora cinnamomi is a pathogen causing root rot in oak trees growing in dehesa sys- tems and also in yellow lupine, a common pasture crop in western Andalusia. In dehesas show- ing different situations in terms of tree decline and disease severity in the lupines, isolation and counting of colonies of P. cinnamomi from soil samples has shown the ability of the herbaceous crop to maintain or increase the inoculum density and thus may enhance oak infections. The obtained results discourage the cultivation of this legume in dehesas with known presence of the pathogen in the soil, whether the trees are suffering the root disease or not.
The following values have no corresponding Zotero field: periodical: Actas de la XLVIII RC de la SEEP. Huesca La multifuncionalidad de los pastos: producción ganadera sostenible y gestión de los ecosistemas pub-location: Huesca
Keywords: decline; Holm oak; root rot; yellow lupine

Genetic diversity of European populations of the oak fine-root pathogen Phytophthora quercina - Cooke, D. E. L.; Jung, T.; Williams, N. a; Schubert, R.; Osswald, W.; Duncan, J. M. (Forest Pathology, 2005)
The recently discovered oak-specific fine root plant pathogen Phytophthora quercina is a significant factor in the current phase of European oak decline but its origins and ecology are poorly understood. A genome-wide analysis of 260 amplified fragment length polymorphism (AFLP) markers was used to examine the genetic diversity of 72 isolates from five oak species at 28 sites in Germany (particularly Bavaria), Italy, France, Hungary and the UK. Within-site diversity was examined at 16 sites. The limited genetic diversity (within and between sites) and lack of genetic substructuring according to geographic origin or host species suggest the rapid spread of a relatively recently introduced species. Two subgroups were distinguished and these may reflect an initial introduction of isolates of two different genetic backgrounds. The relatively low genetic diversity is probably because of the predominantly inbreeding (homothallic) nature of P. quercina. However, evidence of limited intra-site diversity, temporal variation and the lack of clonality within the European population suggest that some diversity is being maintained by occasional outcrossing and turnover of a reservoir of long-lived soil-borne oospore (sexually derived) inoculum
Keywords: AFLP; decline; diversity; pathogen (voyant); Phytophthora

Observations sur la dynamique du développement du Diplodia mutila Fr. apud Mont. sur le chêne-liège, Quercus suber L., au Maroc - El-Badri, Naïma; Abadie, Michel (Cryptogamie Mycologie, 2000)
Mamora forest in Rabat (Morocco) was a wide forest of cork oak which is rapidly disappearing. This crisis is caused by both human exploitation and overgrazing by animals. This situation is also affected by the existence of harmful insects and parasitic fungi. One of the most common species is Diplodia mutila Fr. apud Mont. (group of Coelomycetes) anamorph of Botryosphaeria stevensii Shoem., which causes withering and cankers on trunks and branches. The electron microscope observations on pycnosporogenesis and the study of the relation plant-host-pathogen show the structure and the biological cycle of Diplodia mutila, the endophytic and the systemic development of the pathogen and the irreversible damage on the plant host. This study is a contribution to the research on cork-oak forest protection.
Keywords: decline; Diplodia mutila Fr. apud Mont.; FOREST; Mamora; Morocco; pathology; Quercus suber L.; ultrastructure